PERBANDINGAN TINGKAT KEBUGARAN JASMANI ANTARA SISWA KELAS XI SMA ISLAM BRAWIJAYA, SMA TARUNA NUSA HARAPAN, DAN SMA TAMAN SISWA DI KOTA MOJOKERTO - BUDI RACHMANTO, DIKA (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Physical Education is a compulsory subject in school curriculum, in elementary, junior high and senior school. One of the objection of physical education, sports, and health is providing the opportunity for students to improve their physical fitness. Physical fitness is a physical ability to perform daily physical activities optimally and still be able to perform other physical activities without any significant fatigue. The Purpose of this study was to compare the level of physical fitness among eleventh grade students in Brawijaya Islamic high School, Taruna Nusa Harapan High School, and Taman Siswa High School in Mojokerto. This research uses a quantitative non-experimental using comparative approach called comparative descriptive. The sample in this study are 30 students from each school. Samples taken by cluster random sampling method, one class from each school. To determine the level of physical fitness of students using MFT test or Multistage Fitness Test.    The result of this study, the average level of physical fitness of eleventh grade students in Brawijaya Islamic High School is 30,760. The average level of physical fitness of nine grader students in Taruna Nusa Harapan is 29,077. The average level of physical fitness of nine grader students 27,630. Furthermore, the data were analyzed using Analysis of Variance (ANOVA), if the Sig> alpha (0.05), then H0 is accepted since there is no significant difference. Obtained from SPSS, Sig. 0.242 > alpha (0.05), it can be said that there was no significant difference in the level of physical fitness among nine grader students of Brawijaya Islamic High School, Taruna Nusa Harapan High School, and Taman Siswa High school in Mojokerto. Keywords : Physical Fitness, Multistage Fitness Test (MFT), Students.